EFEKTIVITAS PENGGUNAAN ALAT PERAGA TERHADAP PENINGKATAN PRESTASI BELAJAR SISWA PADA MATERI BANGUN RUANG SISI DATAR (KUBUS DAN BALOK) - Ahmad Ahmad; Ahmad Sehabuddin (Universitas Bumigora, 2018)
A props is a tool when learning. In the case on the subject of plane geometry, props are urgently needed to visualize the material taught by the teacher, so that students can see firsthand the real forms of flat-side building. Learning by using props can focus students and can increase student’s activity and motivation. The purpose of this study is to determine the effectiveness of the use of props in improving student achievement on the subject of plane geometry in class V MI Nurul Yaqin Kelanjur. This research is a quasi-experimental research where the researcher only control the variables in the class. Research method used in this research is quantitative method by using t-test formula. The research population is class V MI Nurul Yakin Kelanjur which amounted to 12 people by given preetest and posttest.Based on the results of hypothesis test data analysis with t-test, it’s found that there are significant differences between student achievement before and after using props, this can be seen from tcount = 3.782 > ttable = 1.717, so H0 rejected. To find out whether the learning by using props effectively or not, seen from the mastery of individual and classical mastery. Students' mathematics learning achievement after using props has been found that many students are 91.67% complete. Because the complete student achieves 85%, the student is said to be thoroughly classical. Based on research result, it can be concluded that learning by using props on the subject of plane geometry effective to do.